Obstetric competence among primary healthcare workers in Mali. Issue 1 (2nd April 2014) - Traoré, Mamadou; Arsenault, Catherine; Schoemaker‐Marcotte, Camille; Coulibaly, Aliou; Huchon, Cyrille; Dumont, Alexandre; Fournier, Pierre
Abstract: Objective: To determine individual and contextual factors associated with emergency obstetric and neonatal care (EmONC) competency among primary healthcare staff in Mali. Methods: Between November 2011 and April 2012, a competency test was administered to 196 healthcare workers in 65 community health centers in Mali. The test was scored from 0 to 100, and differences among 5 areas of EmONC were assessed. A multilevel linear regression model was used to determine individual and contextual factors associated with score. Results: The mean score was 66.7 (minimum, 15.9; maximum, 97.7). Knowledge was most deficient for postpartum infection and hypertensive complications. Type of health worker, years of experience, number of days absent, and availability of guidelines for management of obstetric complications within the health center were positively associated with test score ( P < 0.05). Availability of guidelines was associated with higher competency of physicians, health technicians, and obstetric nurses ( P < 0.001), and seemed to influence the competency of healthcare workers with fewer than 10 years of experience in particular. Conclusion: Guidelines must be developed that will facilitate standardization of the management of postpartum infection and other less common complications for which healthcare workers show low competence. Strategies to increase use of these guidelines will be necessary.